Winter haze amplification by aerosol hygroscopic growth over eastern Indo- Gangetic Plain - Thejas Kallihosur; Vijayakumar S. Nair; P. R. Sinha (Communications Earth & Environment)
Abstract Frequent occurrences of widespread winter haze over Northern India largely appear to originate from exceedingly high concentrations of fine particulate matter from anthropogenic emissions. However, the underlying mechanisms driving winter haze in Northern India are not well understood. This study employed a synergy of satellite and reanalysis data from 2006 to 2021 to assess the role of hygroscopic growth of aerosol optical depth in winter haze over the eastern Indo-Gangetic Plain. A method has been developed to extract dry aerosol optical depth from ambient aerosol optical depth to elucidate the origin of winter haze. About 31% of severe haze episodes (aerosol optical depth > 0.85) occurring under ambient humidity conditions decrease to below 5% for dry conditions, indicating the critical role of particle hygroscopic growth. The change in radiative forcing at the top of the atmosphere due to hygroscopic growth is relatively small compared to that at the surface and in the atmosphere, indicating enhanced atmospheric warming. The ubiquitous winter haze over the eastern Indo-Gangetic Plain is exacerbated by hygroscopic growth under high anthropogenic aerosol emissions, further aggravated through aerosol-radiation feedback. These results will be valuable in devising haze forecasts, implementing effective mitigation policies, and representing aerosol hygroscopicity in climate models.